2009
DOI: 10.1080/10715760903140568
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance (EPR) spectroscopy of the stable-free radical in the native metallo-cofactor of the manganese-ribonucleotide reductase (Mn-RNR) ofCorynebacterium glutamicum

Abstract: Ribonucleotide reductases (RNR; EC 1.17.4.1) provide the 2'-deoxyribonucleotides for DNA replication of proliferating cells by a uniform radical mechanism using diverse metals. The native metallo-cofactor of the Corynebacterium glutamicum RNR contains manganese and is sensitive to EDTA and radical scavengers. Hybrid holoenzymes, capable of ribonucleotide reduction, were composed of the small manganese-containing (R2F) and the large catalytic subunit (R1E) from either of the two corynebacterial RNRs. A syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
4
21
1
Order By: Relevance
“…In neither case was the yield of active enzyme sufficiently high for biophysical characterization. We propose that we have formed in vitro the same NrdF cofactor isolated from C. ammoniagenes , and perhaps more recently from Corynebacterium glutamicum (14). …”
Section: Discussionmentioning
confidence: 71%
“…In neither case was the yield of active enzyme sufficiently high for biophysical characterization. We propose that we have formed in vitro the same NrdF cofactor isolated from C. ammoniagenes , and perhaps more recently from Corynebacterium glutamicum (14). …”
Section: Discussionmentioning
confidence: 71%
“…The induction of mntH is especially pronounced during H 2 O 2 stress, since OxyR directly activates its transcription (Kehres et al ., 2002; Anjem et al ., 2009). Furthermore, in vitro studies have suggested that Corynebacterium glutamicum and Corynebacterium ammoniagenes use manganese for ribonucleotide reductase function (Fieschi et al ., 1998; Abbouni et al ., 2009). If E. coli NrdEF were manganese‐dependent, then the failure of this enzyme to function when the nrdHIEF operon was artificially expressed would be understandable, since manganese is not imported into E. coli under normal growth conditions (Anjem et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Zinc can be erroneously incorporated into the copper-binding protein azurin 39 . Ribonucleotide reductases of various bacteria, upon overexpression in E. coli, contain a dinuclear Fe center, yet in its native state the enzyme possesses a di-manganese center 40,41 . Hence, these data imply that a number of proteins isolated as Zn-binding proteins, may exist as Fe-S proteins inside the cell, emphasizing the importance of assessing the metal occupancy of a protein in its native organism.…”
Section: Discussionmentioning
confidence: 99%